Effects of Mantle Hybridization by Interaction with Slab Derived Melts in the Genesis of Alkaline Lavas across the Back-Arc Region of South Shetland Subduction System - Altunkaynak, Şafak; Aldanmaz, Ercan; Nývlt, Daniel (Oxford University Press (OUP), 2022)
AbstractLate Miocene to Late Pleistocene alkaline lavas in the northernmost part of the Antarctic Peninsula and its off-lying islands are the latest stage of magmatic activity that took place in response to lithospheric extension in the back-arc region of the South Shetland subduction system. The alkaline magmatism occurred much later than the main pulse of Cretaceous arc magmatism and generated basaltic extrusive rocks during several sub-aqueous/sub-glacial and sub-aerial eruption periods. The suite consists primarily of alkali olivine basalts with oceanic island basalt (OIB)-like trace element signatures, characterized by elevated highly to less incompatible element ratios compared to MORB. The samples have higher 87Sr/86Sr (0.70301–0.70365), and lower 143Nd/144Nd (0.51283–0.51294) and 176Hf/177Hf (0.28291–0.28298) than depleted MORB mantle. Their lead isotope ratios vary within a limited range with 206Pb/204Pb, 207Pb/204Pb, 208Pb/204Pb ratios of 18.797–18.953, 15.577–15.634, and 38.414–38.701, respectively. Sr, Nd, Hf and Pb isotope systematics suggest involvement of diverse source materials in the genesis of the alkaline magmas. Evaluation of radiogenic isotope and trace element data indicates that the source of the alkaline melts had a complex petrogenetic history, reflecting the effects of mantle hybridization along the slab mantle interface through interaction of mantle wedge peridotites with volatile-bearing, siliceous melts produced by melting of subducted sediments and basaltic oceanic crust. Hf-Nd isotope and trace element projections further demonstrate that the metasomatizing melt was likely generated by eclogite partial melting at sub-arc to post-arc depths, in equilibrium with a garnet-bearing residue and involved breakdown of high field strength elements (HFSE) retaining phases. Consumption of metasomatic amphibole during partial melting of hybridized peridotite at the wet solidus appears to have had a significant effect on the final melt compositions with high HFSE, Na and H2O contents.